PLCγ1: Potential arbitrator of cancer progression. (January 2018) - Jang, Hyun-Jun; Suh, Pann-Ghill; Lee, Yu Jin; Shin, Kyeong Jin; Cocco, Lucio; Chae, Young Chan
Abstract: Phospholipase C (PLC) is an essential mediator of cellular signaling. PLC regulates multiple cellular processes by generating bioactive molecules such as inositol-1, 4, 5-triphosphate (IP3 ) and diacylglycerol (DAG). These products propagate and regulate cellular signaling via calcium (Ca 2+ ) mobilization and activation of protein kinase C (PKC), other kinases, and ion channels. PLCγ1, one of the primary subtypes of PLC, is directly activated by membrane receptors, including receptor tyrosine kinases (RTKs), and adhesion receptors such as integrin. PLCγ1 mediates signaling through direct interactions with other signaling molecules via SH domains, as well as its lipase activity. PLCγ1 is frequently enriched and mutated in various cancers, and is involved in the processes of tumorigenesis, including proliferation, migration, and invasion. Although many studies have suggested that PLCγ functions in cell mobility rather than proliferation in cancer, questions remain as to whether PLCγ regulates mitogenesis and whether PLCγ promotes or inhibits proliferation. Moreover, how PLCγ regulates cancer-associated cellular processes and the interplay among other proteins involved in cancer progression have yet to be fully elucidated. In this review, we discuss the current understanding of the role of PLCγ1 in cancer mobility and proliferation.